Efektifitas Penyaluran Zakat Pada Masjid Darussalam Kota Wisata Cibubur - Umam, Rifqi Chairul (Institut Agama Islam Negeri Ponorogo, 2021)
Zakah is one of the pillars of Islam that must be implemented, zakah is generally divided into 2, zakah maal and zakah fitrah. A mosque is a place for Muslims to perform worship both in congregation and individually. In Indonesia the mosque is also a place for collecting and distributing zakat funds. This study aims to identify the effectiveness of zakat distribution through mosques (case study of Darussalam Mosque, Kota Wisata, Cibubur). The research method used is descriptive qualitative research methods with primary and secondary data sources that will be obtained from interviews, viewing reports related to zakat, observations, and documentation to Amil in Masjid Darussalam, Kota Wisata, Cibubur. The results of the study show that all indicators, that is right on target, economic improvement, use of funds. with some notes that need to be considered, namely the ZakatPro program must be carried out carefully monitoring and coaching so that mustahik can be more productive, and provide solutions to each mustahik's business problems